Strategies Of Business Actors In The 3t Region : Case Study In Serawai District, Sintang Regency - Carolin, Angelina; Bangun, Wilson; Tjandrasa, Benny Budiawan (Business, Economics dan Entrepreneurship, 2025)
Significant challenges faced by business actors in Serawai District, Sintang Regency, include geographical conditions that are difficult to reach, high prices of goods, and limited electricity supply. The aim of this research is to analyze the strategies that have been implemented by business actors to overcome these challenges. This research uses qualitative research methods in the form of a case study. The data collection technique was in-depth interviews, observation and documentation, as well as sampling using a purposive sampling technique, totaling 30 participants. The results of the analysis show that business actors have succeeded in implementing strategies such as business diversification, developing collaborative networks, and utilizing information technology to increase competitiveness. The findings in this research contribute to the development of business theory in the 3T regions and offer practical guidance for business actors and policy makers. The findings in this research indicate the need for support from the government in providing better infrastructure and providing training to business actors, so that it can encourage sustainable local economic growth, especially in 3T regions.